2018
DOI: 10.1038/s41598-018-27988-9
|View full text |Cite
|
Sign up to set email alerts
|

Social dominance predicts hippocampal glucocorticoid receptor recruitment and resilience to prenatal adversity

Abstract: The developing fetus is highly sensitive to prenatal stress, which may alter Hypothalamic-Pituitary-Adrenal (HPA) axis programming and increase the risk of behavioral disorders. There is high variability among the human population, wherein many offspring of stressed pregnancies display resilience to adversity, while the remainder displays vulnerability. In order to identify biological substrates mediating between resilience or vulnerability to prenatal adversity, we exposed stress-resistant Dominant (Dom) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 87 publications
(121 reference statements)
0
13
0
Order By: Relevance
“…We have previously shown that Sub mice are characterized by a high sensitivity to various stressogenic triggers, including acute [14], chronic mild (CMS) [10], social [15, 16] and prenatal [17, 18] stresses. At physiological and biochemical levels, this stress sensitivity is underlined by the hyper-activation of the HPA axis, resulting in elevated levels of stress- induced corticosterone and in the decreased expression of glucocorticoid receptor (GR), leading to an altered negative feedback regulation of the HPA axis activity [18].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Sub mice are characterized by a high sensitivity to various stressogenic triggers, including acute [14], chronic mild (CMS) [10], social [15, 16] and prenatal [17, 18] stresses. At physiological and biochemical levels, this stress sensitivity is underlined by the hyper-activation of the HPA axis, resulting in elevated levels of stress- induced corticosterone and in the decreased expression of glucocorticoid receptor (GR), leading to an altered negative feedback regulation of the HPA axis activity [18].…”
Section: Discussionmentioning
confidence: 99%
“…Paroxetine showed dose dependent anti-depressive-like effect in Sub mice and caused a paradoxical effect in Dom mice. Sub mice serve as an animal model of depression demonstrating depressive-like behavior and are susceptible to stressful stimuli, whereas Dom mice exhibit strong characteristics of manic-like behavior and show pronounced stress resilience [180,183]. The altered monoamine content in brain areas referring to emotionality and social hierarchy underly the behavioral phenotype in Sub and Dom mice.…”
Section: Genetically Selected Flinders Sensitive Line (Fsl) Rat Modelmentioning
confidence: 99%
“…Using comprehensive behavioral and pharmacological approaches 29 , 32 , we previously demonstrated that dominant (Dom) and submissive (Sub) mice differentially respond to psychotropic agents 29 and stressogenic 30 , possess different life spans 33 , distinct brain neurochemistry 34 , and cognitive and learning capabilities 35 . More specifically, while Dom mice are relatively stress resilient, Sub mice exhibit strong sensitivity to stress 30 , alongside depressive-like and anti-social 30 characteristics 36 , as well as systematic inflammation, demonstrated by higher interleukin (IL)-6 and IL-1b serum levels 33 . The multi-aspect differences between Dom and Sub animals led us to hypothesize that these mice possess different gut microbiome compositions, which may play a crucial role in shaping their social behavior by inducing inflammation leading to alterations in adipose tissue physiological homeostasis.…”
Section: Introductionmentioning
confidence: 99%